Adaptación de lente de contacto post implante de anillos intraestromales en paciente masculino de 15 años. - Bazán Aguilera, Ronny Josué (2023)
The present study developed in a 15-year-old male patient with contact lens adaptation post implantation of intrastromal rings, who suffers from keratoconus, which is a condition or pathology that is evident in the structure of the cornea, where it undergoes an alteration and causes distortion of vision. This non-inflammatory disease causes a malformation in the morphology of the cornea. In the development of the clinical case, it was established to determine the visual acuity and adapt the patient to contact lenses, in this clinical case an adolescent is presented who is referred by the ophthalmologist after having been intervened for the application of intrastromal rings. to correct corneal problems caused by eye rubbing and prolonged time on electronic devices. He went to the consultation presenting a clinical picture of headache, visual acuity, blurred distant vision, constant tearing. In the development, diagnostic methods such as ocular refraction, corneal topography, Schirmer test and staining of the eye with fluorescein were performed. Subsequently, the adaptation of toric contact lenses was used according to the visual acuity presented by the patient, eye washing was performed with ringer's solution and disinfectant drops to prevent any infection. The patient presented a rapid improvement in his visual acuity, thus adapting to toric contact lenses and improving his well-being, managing to improve visual clarity from a distance and the symptoms disappeared as the days went by.